Quality assessment of furosemide tablet generics used in a teaching hospital in Nigeria - Abdurrahman Umar; Halimatu Sadiya Hassan; Salisu Awwalu (African Journal of Pharmaceutical Research and Development (AJOPRED))
The use of ineffective and poor-quality drugs endangers treatment leading to treatment failure. For the desired therapeutic effect, drugs should contain the appropriate amount of active pharmaceutical ingredients and the required physicochemical properties. This study aimed to evaluate the quality as well as the physicochemical properties of different generics of furosemide tablets used in a teaching hospital in Nigeria. Five different generics of furosemide tablets were purchased from different pharmacy units in the hospital. Their qualities were assessed via identification, assay, weight variation, friability, disintegration and dissolution tests using British Pharmacopoeia standards. All samples contain the stated active pharmaceutical ingredients, however, only two generics have furosemide within the 95 – 105% BP official limit. The weight variation test results indicated that two generics failed to comply with BP specification limits. The generics were found to be able to withstand the rigour of transportation as indicated by their friability values of less than 1 %. The generics were also found to be immediate release tablets as showed by their rapid disintegration time of less than 2 minutes. All the generics released more than 80 % furosemide within 60 minutes. Only two out of the five furosemide generics passed the quality assessment and are therefore expected to yield the desired therapeutic effect.